An assumption of in situ resource utilization for “bio-bricks” in space exploration - Zuo, Hongyan; Ni, Shuisong; Xu, Meiying (Frontiers in Materials, 2023)
Microbially Induced Carbonate Precipitation (MICP) mimics the natural cementation process occurring in various geological settings by using bicarbonate minerals resulting from various bacterial metabolic pathways as cementing agents. This bio-technique can be used to manufacture the so-called bio-bricks, which rival the regular bricks in strength and durability. In the last two decades, MICP has been increasingly utilized for the maintenance and repair of infrastructures on earth. More recently, this process has also been shown to have great potential as an energy saving and cost-effective means for in-situ resource utilization (ISUR) for the production of construction materials for developing extraterrestrial human settlements for space programs such as lunar exploration. In this review, the description of natural cementation, the anaerobic and aerobic bacterial metabolic activities leading to calcium carbonate precipitation, the properties of regolith on the Moon, the production of bio-bricks, and potential research needs are reviewed.